PENGENTASAN KEMISKINAN DI DESA MAUBOKUL MELALUI PEMBERDAYAAN BERBASIS KEWIRAUSAHAAN SOSIAL - Ramompas, Yuvensius; Renggo, Yuniarti Reny; Kelen, Lusianus Heronimus Sinyo; Meiyasa, Firat; Ndahawali, Suryaningsih; Putra, Jovan Imanuel; Lili, Andreas Kalukur (Jurnal Abdi Insani, 2024)
The government under the leadership of President Joko Widodo attempted to reduce poverty by making poverty alleviation programs a national strategy. The poverty rate in rural areas is consistently higher than the poverty rate in urban areas, this is an indication that efforts to reduce poverty rates in rural areas are still encountering obstacles. One effort that can reduce poverty rates in villages is through empowerment. Program Kemitraan Masyarakat (PKM) empowerment based on social entrepreneurship in Maubokul village aims to increase collective independence and prosperity. The series of activities includes several method stages, namely the preparation and social analysis stages, the implementation stages, the mentoring, monitoring and evaluation stages, and the collaboration and partnership stages. This service was carried out through collaboration between the Maubokul Village government and the PKM team. The research results show that training and guidance activities in fish farming have the potential to increase income and food security through a culture of social entrepreneurship, thereby helping to build the village economy. The village government, in collaboration with the PKM team, is helping to accelerate poverty reduction by collaborating through empowerment and training for the community. It is hoped that in future activities we can develop and continue programs that have been implemented and those that have not been implemented optimally.